Synthesis And Characterization Of Complex Diaquadihydantoin Nickel(II) Sulfat Monohidrat - Sentot Budi Rahardjo; Surya Dewi Marliyana; Nur Asih Siwi Wulandari (ALCHEMY Jurnal Penelitian Kimia, 2014)
The purpose of the research is to find out the synthesis, formula and characteristic of complex of Nickel(II) with hydantoin (hyd). Complex of nickel(II) with  hydantoin  have been synthesized in 1 : 1 mole ratio of metal to ligan in methanol.The formula of  complex which are predicted from analysis of % Ni in complex by Atomic Absorption Spectroscopy (AAS) is Ni(hyd)2(H2O)3.SO4.  Ratio  of  cation  and  anion  of  complex  is  measured  by conductivitymeter  correspond to 1: 1.  The thermal analysis  is determined  by Differential Thermal  Analyser  (DTA)  indicate  that  complex  contain  some  hydrate,  thus  possibility formula  of  complex  is  [Ni(hyd)2(H2O)2]SO4.H2O (Diaquadihydantoinnikel(II) sulfat monohidrat).  Data  of  infra  red  spectra  show  a  shift  of  N-H  group  and  tertier  N  group 138 absorption  and  indicate  this  functional  group  coordinated  to  the  center  ion.  Magnetic Suscepbility measurement show that the complex is paramagnetic with μeff  = 3.2  BM. The UV-Vis spectra appear do to 2 transition peak on  λ  =  740 nm (13,513 cm-1) and  405 nm (24,691 cm-1).  The peak indicate that structure of complex is octahedral with transition 3A2g→ 3T1g(P)(ν2) andtransition 3A2g  → 3T1g(F)(ν3). One peak which  is  not appear is transition 3A2g → 3T2g (F)(ν1) which also estimate of 10 Dq (Δ0) is 103.615 kJ mol-1.